CITOKINE RELEASE SYNDROME MANAGEMENT IN ADULTS AND PEDIATRIC PATIENTS - Garcia, Julia Lopes; Rodrigues Kerbauy, Fabio (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2022)
Chimeric Antigen Receptor (CAR) T cell therapy has demonstrated efficacy in B cell malignances. However, the treatment is not harmless and, in some patients, can lead to a fatal endpoint. For this reason, the knowledge and the early recognition and management of the side effects related to CAR-T cell therapy for the multidisciplinary team is essential. In this article, we have summarized the current recommendations for identification, gradation and management of cytokine release syndrome related to CAR-T cell therapy.